Rancang Bangun Sistem Informasi Penjualan Toko Eight Point Store Berbasis Website - Kristianti, Novera; Rahman, Resha Ananda (Universitas Palangka Raya, 2022)
E-commerce can be interpreted as a way of using internet facilities for online shopping or trade or direct sales, where a website can provide